NEW WAYS OF PEER REVIEWING IN JOURNALS: OPEN REVIEW - Andrea Mora-Campos (Pensar en Movimiento)
Technology has helped improve many aspects of the quality of publications: more visibility, greater access to sources of information and option to verify those sources, among others. This has meant that some journals have had to adjust their processes, especially peer reviewing. The blind mode is the method most commonly used by journals. In the case of our journal, we have traditionally used the double-blind style; however, we have noticed that, with advanced Internet, social networks, and media, it is easier for reviewers to obtain previews, preprints, primary research or previous articles that can help identify the author, thus making the double blind review difficult. These experiences have made us analyze whether the peer review system used by the journal is appropriate. Searching for other peer review options we found the open review. This paper briefly reviews some advantages and disadvantages of this type of review and the experience faced by this journal when implementing it.